2016
DOI: 10.1039/c6sc90045c
|View full text |Cite
|
Sign up to set email alerts
|

Correction: Iminoboronates are efficient intermediates for selective, rapid and reversible N-terminal cysteine functionalisation

Abstract: Correction for ‘Iminoboronates are efficient intermediates for selective, rapid and reversible N-terminal cysteine functionalisation’ by Hélio Faustino et al., Chem. Sci., 2016, 7, 5052–5058.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Significant drawbacks of this chemistry are slow kinetics and undesirable acidic reaction conditions . Recently, two research groups reported that 2‐acetyl benzene boronic acids (2ABBAs) could resolve such issues, even under neutral pH conditions . From those studies, it turned out that N−B coordination in iminoboronates not only stabilized an intermediate energy state, but also accelerated the kinetics of this reaction.…”
Section: Methodsmentioning
confidence: 99%
“…Significant drawbacks of this chemistry are slow kinetics and undesirable acidic reaction conditions . Recently, two research groups reported that 2‐acetyl benzene boronic acids (2ABBAs) could resolve such issues, even under neutral pH conditions . From those studies, it turned out that N−B coordination in iminoboronates not only stabilized an intermediate energy state, but also accelerated the kinetics of this reaction.…”
Section: Methodsmentioning
confidence: 99%
“…We further synthesized a new BAA derivative bearing a biotin (BAA-biotin) to test the potential applicability of BAA chemistry for labeling large peptides or proteins. The therapeutic peptide salmon calcitonin containing 32 amino acids and a disulfide bond formed between an N-terminal and an internal Cys residue was selected as an example . Calcitonin (100 μM) was treated first with excessive TCEP to reduce the disulfide bond and subsequently with equivalent BAA/BAA-biotin and NaBH 3 CN (5 equiv).…”
Section: Resultsmentioning
confidence: 99%
“…Another reaction relying on selective thiazolidine formation between aldehyde and 1,2-aminothiol has also been widely used, which however takes long reaction times under acidic conditions . The reaction rate can be greatly accelerated using benzaldehyde bearing an ortho-boronic acid substituent to promote formation of a boronated thiazolidine, though aryl boronates can be subject to rapid oxidation by endogenous hydrogen peroxide in living systems . In addition, the reaction between 2-cyanobenzothiazole (CBT) and Cys, which is the last step of the synthesis of d -luciferin, has been developed into a useful ligation strategy for protein labeling and functional macrocycle construction. ,, Recently, N -hydroxysuccinimide activated acrylamide has been designed and synthesized for both the functionalization of N-terminal Cys and the cyclization of in-chain or C-terminal Cys and nearby lysine (Lys) residues .…”
Section: Introductionmentioning
confidence: 99%
“…The use of ortho-boronic acid substituted benzaldehydes such as reagents such as 2-formyl phenylboronic acid (2-FPBA) allows us to overcome the drawbacks of thiazolidine ligation. 2-FPBA promotes the fast formation of a thiazolidino-boronate (TzB) conjugate by reacting with the N-terminal cysteine at neutral pH and in equimolar ratio between the protein and the probe derivative [36,75] (Figure 2d). Notably, the TzB product was found to exhibit superior stability at physiological pH with respect to thiazolidine conjugates due to boron coordination by the thiazolidine ring.…”
Section: Chemical Strategies Targeting Protein N-terminus 21 Direct Labeling Of Protein N-terminusmentioning
confidence: 99%
“…Notably, the TzB product was found to exhibit superior stability at physiological pH with respect to thiazolidine conjugates due to boron coordination by the thiazolidine ring. Conveniently, TzB may dissociate in the presence of benzyl hydroxylamine [75] and at acidic pH [36]. This latter feature makes the TzB chemistry interesting for the development of pH responsive drug-conjugates such as antibody-drug conjugates designed to selectively release the cytotoxic payload in the endosomes.…”
Section: Chemical Strategies Targeting Protein N-terminus 21 Direct Labeling Of Protein N-terminusmentioning
confidence: 99%